Studi Indeks Eritrosit Pada Pasien Diagnosis Positif Malaria - Fitriani kahar; Djoko Priyatno; Beatrix Marta Meo (Politeknik Kesehatan Kemenkes Makassar, 2020)
Malaria is a contagious disease caused by parasites (protozoa) of the genus Plasmodium, which can be transmitted through the bite of a female Anopheles mosquito. There are 4 species of Plasmodium that cause malaria in humans, namely Plasmodium Vivax, Plasmodium Falciparum, Plasmodium Malariae and Plasmodium Ovale. Malaria is an infectious disease that is found in many tropical and sub-tropical countries. This study aims to determine the description of the erythrocyte index in patients diagnosed with malaria positive at the Kotaratu Public Health Center, Ende Utara District. Erythrocyte index examination functions in determining the type of anemia. This research method is laboratory observation with a descriptive approach. The research sample was 20 patients with positive diagnosis of malaria in Kotaratu Public Health Center, Ende Utara District. The results of this study were 20 samples, for normal MCV values 10 samples (50%), 10 samples (50%) less than normal and 0 samples (0%) more than normal. The MCH value was less than normal for 7 samples (35%), 13 samples (65%) normal and 100% normal MCHC value. The conclusion is that in malaria parasite infection there is a low MCV is 50% and 50% normal, low MCH is 35%, and normal is 65, while normal MCHC is 100%. Keywords: Erythrocyte Index (MCV, MCH, MCHC), Malaria